TINGKAT SERANGAN HAMA PENGGEREK POLONG, Maruca testulalis Geyer (Lepidoptera: Pyralidae)) PADA DELAPAN VARIETAS KACANG HIJAU (Vigna radiata L.) DAN PENGARUHNYA TERHADAP HASIL - Minal Faizin; Nadrawati Nadrawati; Edhi Turmudi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE INCIDENCE OF POD-BORER, Maruca testulalis Geyer (Lepidoptera: Pyralidae) IN EIGHT MUNG BEAN VARIETIES (Vigna radiata L.) AND ITS EFFECT ON YIELD]. Mung beans are an essential food crop in Indonesia, whose production is still increasing to meet domestic needs. However, the high attack of plant pests Maruca testulalis Geyer (Lepidoptera: Pyralidae) is one of the leading causes of the low production of green beans. The use of superior varieties is one solution to controlling these pests. This study was conducted to test seven superior varieties of green beans, namely Vima 1, Vima 2, Vima 3, Murai, Kenari, Kutilang and Seriti and one local variety against M. testulalis. The study used a completely randomized block design and was repeated three times. The results showed that the mungbean varieties Vima 1, Vima 2, and Vima 3 had M. testulalis attack with the lowest level of seed damage in sequence, namely 5.84%, 7.94%, and 6.39%. Even though the percentage of pod borers attack did not significantly affect the growth of all Balitkabi superior varieties and one local variety of mungbean planted, the Kutilang variety was the highest yield with seed yield rates that were as low as other low-attack varieties.